Lessons from two series by physicians and caregivers' self-reported data in DDX3X-related disorders - Ruault, Valentin; Burger, Pauline; Gradels-Hauguel, Johanna; Ruiz, Nathalie; Xtraordinaire; Jamra, Rami Abou; Afenjar, Alexandra; Alembik, Yves; Alessandri, Jean-Luc; Arpin, Stéphanie; Barcia, Giulia; Bendová, Šárka; et al. (Molecular genetics & genomic medicine, 2024)
INTRODUCTION AND METHODS: We report two series of individuals with DDX3X variations, one (48 individuals) from physicians and one (44 individuals) from caregivers. RESULTS: These two series include several symptoms in common, with fairly similar distribution, which suggests that caregivers' data are close to physicians' data. For example, both series identified early childhood symptoms that were not previously described: feeding difficulties, mean walking age, and age at first words. DISCUSSION: Each of the two datasets provides complementary knowledge. We confirmed that symptoms are similar to those in the literature and provides more details on feeding difficulties. Caregivers considered that the symptom attention-deficit/hyperactivity disorder were most worrisome. Both series also reported sleep disturbance. Recently, anxiety has been reported in individuals with DDX3X variants. We strongly suggest that attention-deficit/hyperactivity disorder, anxiety, and sleep disorders need to be treated.
Keywords: DDX3X; hyperkinetická porucha; caregivers; Attention Deficit Disorder with Hyperactivity; lidé; Infant; zpráva o sobě; Self Report; ADHD; předškolní dítě; developmental milestones; osoby pečující o pacienty; kojenec; Caregivers; Child, Preschool; DEAD-box RNA-helikasy; DEAD-box RNA Helicases; Humans